Time-varying expected returns : evidence from the U.S. and the U.K - Sousa, Ricardo M. (2010)
I assess the relative performance of several empirical proxies developed in the literature of asset pricing to capture time-variation in expected future returns using data for the U.S. and the U.K.. I show that the wealth composition risk by Sousa (2010) exhibits strong forecasting power.